Analysis of flowering gene in palm oil (Elaeis guineensis) - FAIZAL, IRVAN; EMDI, AXEL (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2017)
Faizal I, Emdi A. 2017. Analysis of flowering gene in palm oil (Elaeis guineensis). Asian J Agric 1: 53-58. Palm oil has always been an important commodity in Indonesia. The most common species is palm oil, Elaeis guineensis. Palm oil is a monoecious plant with a tendency to be a temporal dioecious. Female flower will be the one that produces palm oil fruit, that later is treated with palm oil while male flower only takes part in the fertilization process. In order to know the ratio between female and male flower tree in a plantation, this study was performed to detect a distinction between female and male flowering gene sequences from DNA sample of E. guineensis. Based on previous study which managed to characterize MADS-box gene of palm oil, a primer was designed and named GmG (Globosa-male-Gaps). The result shows that the primer has the ability to differentiate DNA sequence female and male flower of E.guineensis, Palm oil. However, further studies with full sequence and more samples are needed to find distinctive results between female and male flower sequences as the GmG primer could be used to design a specific marker or primer to detect the presence of female or male flower within a tree.